A Course in Digital Libraries - Yerkey, A. Neil; Jorgensen, Corinne (DESIDOC Journal of Library & Information Technology, 2002)
The paper describe the objectives, topical content, and reasons for developing a course on digital libraries. The Internet is changing the way librarians view information sources. The ideas of the library as a place is being questioned while the 'library without walls" is rapidly emerging. The course provides a broad overview of technical and professional issues related to digital libraries. It leads students through a theoretical discussion of various facets, and gives practical experiences with tools necessary for creation and use of information resources in networked digital formats. http://dx.doi.org/10.14429/dbit.16.1.3246